Efektivitas dan Dampak Program Desa Tani dalam Pemberdayaan Ekonomi Masyarakat di Desa Cibodas Kecamatan Lembang, Kabupaten Bandung Barat - Tia Setiawati (Bandung Conference Series: Economics Studies, 2022)
Abstract. Community economic empowerment is important, because with community empowerment it is one of the efforts to improve welfare and instill more abilities of farmers. The problems felt by the farmers are caused by three factors, namely minimal capital, technology and information, land ownership and human resources (HR). The focus of this study aims to determine how the level of effectiveness and impact of the Desa Tani Program in empowering the economy of the community in Cibodas Village, Lembang District, West Bandung Regency. Respondents in this study amounted to 27 people. The effectiveness data analysis technique uses the effectiveness formula and the impact uses the Wilcoxon Difference Test analysis. The type of analysis used is descriptive quantitative using primary data and secondary data with data collection techniques collected through field surveys using a questionnaire instrument. The analysis method shows that the effectiveness and impact of the Farmer Village Program in empowering the community's economy in Cibodas Village, Lembang District, West Bandung Regency is quite good. The Village Farmer Program has a positive impact on the economic empowerment of the community in Cibodas Village, where farmers have access to strengthening production factors, strengthening production and marketing infrastructure, economic capacity and the ability to access welfare benefits. Abstrak. Pemberdayaan ekonomi masyarakat merupakan hal yang penting, karena dengan adanya pemberdayaan masyarakat hal tersebut salah satu upaya untuk meningkatkan kesejahteraan dan menanamkan kemampuan lebih para petani. Permasalahan yang dirasakan para petani ini disebabkan oleh tiga faktor yakni minim permodalan, teknologi dan informasi, kepemilikan lahan dan sumber daya manusia (SDM). Fokus penelitian ini bertujuan untuk mengetahui bagaimana tingkat efektivitas dan dampak Program Desa Tani dalam pemberdayaan ekonomi masyarakat di Desa Cibodas Kecamatan Lembang, Kabupaten Bandung Barat. Responden dalam penelitian ini berjumlah 27 orang. Teknik analisis data efektivitas menggunakan rumus efektivitas dan dampak menggunakan analisis Uji Beda Wilcoxon. Jenis analisis yang digunakan adalah deskriptif kuantitatif menggunakan data primer dan data sekunder dengan teknik pengumpulan data yang dikumpulkan melalui survei lapangan dengan menggunakan instrumen kuesioner. Metode analisis menunjukkan efektivitas dan dampak Program Desa Tani dalam pemberdayaan ekonomi masyarakat di Desa Cibodas Kecamatan Lembang Kabupaten Bandung Barat sudah cukup baik. Program Desa Tani memberikan dampak positif terhadap pemberdayaan ekonomi masyarakat di Desa Cibodas, di mana para petani mendapatkan akses terhadap penguatan faktor-faktor produksi, penguatan prasarana produksi dan pemasaran, kemampuan ekonomi serta kemampuan mengakses manfaat kesejahteraan.